2017
DOI: 10.1002/cpdd.387
|View full text |Cite
|
Sign up to set email alerts
|

Phase 1, Randomized, Double‐Blind, Placebo‐Controlled Studies on the Safety, Tolerability, and Pharmacokinetics of Naldemedine in Healthy Volunteers

Abstract: Naldemedine (S-297995) is a peripherally acting μ-opioid receptor antagonist for the treatment of opioid-induced constipation, a common side effect of opioid therapy. We determined the safety, tolerability, and pharmacokinetic profiles of oral naldemedine in healthy volunteers in 2 randomized, double-blind, placebo-controlled, phase 1 studies. In the single ascending dose study, subjects received a single dose of naldemedine (0.1-100 mg; n = 42) or placebo (n = 14). In the multiple ascending dose study, subjec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
45
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 18 publications
(48 citation statements)
references
References 21 publications
(37 reference statements)
3
45
0
Order By: Relevance
“…10 No major safety or tolerability issues were observed in either study. 10,11 Another phase 1 study, in which healthy subjects were administered 2 mg of [oxadiazole-14 C]-or [carbonyl-14 C]-naldemedine, showed that nor-naldemedine was the primary metabolite observed in the plasma and accounted for 9% to 13% of the systemic exposure of unchanged naldemedine. 10,11 Another phase 1 study, in which healthy subjects were administered 2 mg of [oxadiazole-14 C]-or [carbonyl-14 C]-naldemedine, showed that nor-naldemedine was the primary metabolite observed in the plasma and accounted for 9% to 13% of the systemic exposure of unchanged naldemedine.…”
mentioning
confidence: 88%
See 4 more Smart Citations
“…10 No major safety or tolerability issues were observed in either study. 10,11 Another phase 1 study, in which healthy subjects were administered 2 mg of [oxadiazole-14 C]-or [carbonyl-14 C]-naldemedine, showed that nor-naldemedine was the primary metabolite observed in the plasma and accounted for 9% to 13% of the systemic exposure of unchanged naldemedine. 10,11 Another phase 1 study, in which healthy subjects were administered 2 mg of [oxadiazole-14 C]-or [carbonyl-14 C]-naldemedine, showed that nor-naldemedine was the primary metabolite observed in the plasma and accounted for 9% to 13% of the systemic exposure of unchanged naldemedine.…”
mentioning
confidence: 88%
“…10,11,22 Therefore, prior and concomitant medications were recorded, and P-gp receptor and CYP3A enzyme inhibitors were prohibited from 2 weeks before admission to the clinical research units until study completion. 10,11,22 Therefore, prior and concomitant medications were recorded, and P-gp receptor and CYP3A enzyme inhibitors were prohibited from 2 weeks before admission to the clinical research units until study completion.…”
Section: Study Populationmentioning
confidence: 99%
See 3 more Smart Citations